(untitled) (Teacher Half-Yearly Journal, 2025)
This study compares sustainable development with Buddhist philosophy to demonstrate how traditional knowledge can guide and encourage the successful evolution of human economies. The sustainable development concept, which emphasized continuous economic growth as the sole solution to environmental and social issues, lacked authenticity. Hermeneutic philosophy served as the study’s guidance. The data from the literature review was examined using a qualitative method of data analysis known as thematic analysis. The "Eighth Fold Path" emphasizes wisdom and moral principles with a sufficiency economy, while capitalism focuses on self-interest. Child labor and misery exist in industrialized economies, with more than 700 million people living in misery and poverty. Buddhism tackles the conflict between economic systems and environmental sustainability by emphasizing the sufficiency economy, no-self, and dependent origination theory. The Buddhist theory of sufficiency economy, or sustainable development, improves by protecting natural capital, increasing social and human capital, and encouraging extensive self-awareness of well-being. The study’s findings and conclusion highlight the importance of implementing the Buddhist sustainable development goal among government, researchers, teachers, students, and community because it promotes a sustainable economy, environmental protection, and development, aligns with the 2030 Agenda, and fosters moral discipline and wisdom for sustainable living. The new paradigm necessitates that further research in these fields be investigated, particularly experimental studies on genuine comparisons to Buddhist eco-friendly sustainability and financial sustainability.